Feasibility Analysis of Inquiry-Based Physics Teaching Modules to Improve The Collaboration Skills of Class XI MAN 2 Lubuklinggau - Yurike Yuniar; Endang Lovisia; Yaspin Yolanda (CV. Dharma Samakta Edukhatulistiwa, 2024)
The aim of this research is to determine the feasibility of an inquiry-based teaching module to improve the collaboration skills of class XI students at MAN 2 Lubuklinggau. The research method used is the 4D development model consisting of 1) Define, 2) Design, 3) Develop and 4) Disseminate. The instrument used to answer the research objectives is the feasibility sheet consisting of a media expert validation sheet, a language expert validation sheet and a material expert validation sheet. The data in this study were analyzed using the Widoyoko formula. Based on the data obtained from the results of the feasibility of inquiry-based teaching modules, a score of 51 was obtained from media experts with a very good classification, a score of 73 from language experts with a very good classification, and a score of 47 from material experts with a very good classification. So the inquiry-based teaching module is declared very suitable for use and able to improve students' collaboration skills.